The Unification of the Fundamental Interactions (International Journal of Scientific Research and Management (IJSRM), 2021)
The known fundamental interactions of nature are to be examined for mathematical connections existing among themselves. This would be a further indication that nature has a mathematical basic framework. The investigation shall show whether a unification of the fundamental forces is reasonable and possible.